Unraveling the cellular heterogeneity of malignant pleural mesothelioma through a deconvolution approach. (4th July 2019) - Blum, Yuna; Jaurand, Marie-Claude; De Reyniès, Aurélien; Jean, Didier
ABSTRACT: We determined the proportions of epithelioid-like and sarcomatoid-like cellular entities within malignant pleural mesothelioma samples, by deconvolution of their transcriptomes. These proportions are associated with prognosis and may guide therapeutic strategies. This novel approach describes both intra- and inter-tumor heterogeneity and provides a new way of thinking about cancer pathology.